SPADE Model to improve Mathematics Learning Outcomes in Elementary Schools - Aan Widiyono; Aliva Rosdiana (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
The purpose of this study is to improve mathematics learning outcomes in geometry at SDN Prawoto 02 Pati through the SPADE model in the 2021/2022 academic year. The research design used a quantitative one-group pretest-posttest design. The research sample is 32 students. The test data for learning mathematics results in the form of multiple choice with a total of 25 questions. Data analysis using t-test. The results showed that there was an increase in student learning outcomes by applying the SPADE model which was seen from the pretest and posttest scores on the geometry material. Judging from the mean value of the pretest of students numbered 58.5 while, the average value of the posttest was 76.2. The increase in the pretest and posttest scores was 17.7. The increase is by t-test with a value of (2-tailed) < 0.05 or 0.000 < 0.005 so that H0 is rejected and Ha is accepted. The results of this analysis can be obtained that the use of camtasia media is very effective because it can improve mathematics learning outcomes optimally.